Extraction of Pandanus amaryllifiolus Roxb.: A review of methods and the influencing factors - Qomarudin Qomarudin (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Pandanus amaryllifiolus Roxb is a tropical plant. Pandan leaves offer potential, especially for their function as a source of natural colors, aroma, and antioxidants. 2-Acetyls-1-pyrroline is the primary fragrance compound in pandan leaves. This scent is essential since it acts as the primary contribution of favorable substances which could be good for physical condition and provide flavor for food products. Its sweetness and flavorful taste are known as a natural origin of flavoring. Some previous studies have carried out standard extraction techniques such as maceration, percolation, reflux, and soxhlet in the extraction process of Pandan leaves. However, the process and results come out differently than the current techniques. The modern technique results in an effective extraction moment, and the solvent used is less than in conventional methods. Hence, this paper discussed several highly good methods, such as ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), and supercritical fluid extraction (SFE). The extraction procedure is governed by some aspects that determine the extraction results. The proper extraction method selection also affects the extraction effectiveness. Therefore, enhancing the profitable value of pandan plants can lead to discovering a better-quality extraction technique.